Language, society and new media - Danesi, Marcel, 1946- author.
1 online resource
Keywords: This book presents an interdisciplinary approach to the scientific study of the relation between language and society, language and culture, language and mind. It integrates frameworks from sociolinguistics and linguistic anthropology and emerging strands of research on language and new media, in order to demonstrate how language undergirds human thought and social behaviors. It is designed as an introductory textbook aimed at students with little to no background in linguistics. Each chapter covers the main aspects of a particular topic or area of study, while also presenting future avenues of study. This edition includes discussions on: social media and the creation of identity; gestural communication; emoji writing; multimodality; human-computer interaction. Discussions are supported by a wealth of pedagogical features, including sidebars, as well as activities, assignments, and a glossary at the back. The overall aimis to demonstrate the dynamic connections between language, society, thought, and culture, and how they continue to evolve in today's rapidly changing digital world. It is ideal for students in introductory courses in sociolinguistics, language and culture, and linguistic anthropology.